2017
DOI: 10.1097/inf.0000000000001649
|View full text |Cite
|
Sign up to set email alerts
|

Weak HIV Antibody Responses in Perinatally Infected Young Adults

Abstract: We compared the antibody response to HIV using two serologic cross-sectional incidence assays in adults with perinatally-acquired HIV, to elite controllers and individuals exposed to antiretroviral therapy who were all infected as adults. Low antibody responses were seen more frequently in adults with perinatally-acquired HIV, both overall and when stratified by viral suppression status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[ 36 , 37 ] Some studies showed a weak antibody response in a proportion of patients with early ART and fewer patients starting ART in chronic HIV infection. [ 38 ] In addition, patients with long-term suppressive ART still had continuous antigenic stimulation and lead to the evolution of HIV-specific antibody. [ 37 ] In our study, patients with VF prior to switch might have different HIV-specific antibody responses compared with patients without VF, further study should focus on the trend of antibody responses to HIV and give some hints to HIV incidence surveillance and vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 , 37 ] Some studies showed a weak antibody response in a proportion of patients with early ART and fewer patients starting ART in chronic HIV infection. [ 38 ] In addition, patients with long-term suppressive ART still had continuous antigenic stimulation and lead to the evolution of HIV-specific antibody. [ 37 ] In our study, patients with VF prior to switch might have different HIV-specific antibody responses compared with patients without VF, further study should focus on the trend of antibody responses to HIV and give some hints to HIV incidence surveillance and vaccine development.…”
Section: Discussionmentioning
confidence: 99%